Impact of Dialysate Calcium Concentration on Clinical Outcomes in Incident Hemodialysis Patients. Issue 40 (October 2015) - Kim, Hyung Wook; Kim, Su-Hyun; Kim, Young Ok; Jin, Dong Chan; Song, Ho Chul; Choi, Euy Jin; Kim, Yong-Lim; Kim, Yon-Su; Kang, Shin-Wook; Kim, Nam-Ho; Yang, Chul Woo; Kim, Yong Kyun
Abstract : Abstract: The association between dialysate calcium (DCa) concentration and mortality in hemodialysis (HD) patients is controversial. In this study, we evaluated the impact of DCa concentration on mortality in incident HD patient. Incident HD patients were selected from the Clinical Research Center registry—a prospective cohort study on dialysis patients in Korea. Patients were categorized into 3 groups according to the prescribed DCa concentration at the time of enrollment. High DCa was defined as a concentration of 3.5 mEq/L, mid-DCa as 3.0 mEq/L, and low DCa as 2.5 to 2.6 mEq/L. The primary outcome was all-cause mortality and secondary outcomes were cardiovascular or infection-related hospitalization. A total of 1182 patients with incident HD were included. The number of patients in each group was 182 (15.4%) in high DCa group, 701 (59.3%) in the mid-DCa group, and 299 (25.3%) in the low DCa group. The median follow-up period was 16 months. The high DCa group had a significantly higher risk of all-cause mortality compared with the mid-DCa group (hazard ratio [HR] 2.23, 95% confidence interval [CI] 1.28–3.90, P  = 0.005) and the low DCa group (HR 3.67, 95% CI 1.78–7.55, P  < 0.001) after adjustment for clinical variables. The high DCa group was associated with higher risk of cardiovascular and infection-related hospitalization compared with the low DCa group (HR 3.25, 95% CI 1.53–6.89, P  = 0.002; and HR 2.77, 95% CI 1.29–5.94, P  = 0.009, respectively). Of these 1182 patients, 163 patients from each group were matched by propensity scores. In the propensity score matched analysis, the high DCa group had a significantly higher risk of all-cause mortality compared with the mid-DCa group (HR 2.52, 95% CI 1.04–6.07, P  = 0.04) and the low DCa group (HR 4.25, 95% CI 1.64–11.03, P  = 0.003) after adjustment for clinical variables. Our data showed that HD using a high DCa was a significant risk factor for all-cause mortality and cardiovascular or infection-related hospitalization in incident HD patients.